ANALISIS PERSONAL BRANDING BEAUTY CONTENT CREATOR ADHELIA FA PADA MEDIA SOSIAL (ANALISIS KONTEN KUALITATIF PADA AKUN INSTAGRAM @BLACKXUGAR) - Nadya Andrani; Baiq Vira Safitri; Yy Wima Riyayanatasya (Program Studi Ilmu Komunikasi Universitas Mataram, 2023)
ABSTRACT Social media especially instagram, can be used to build personal branding for each user, such as beauty content creator Adhelia Fa on Instagram @blackxugar who shows her identity in her interest in beauty according to her version by uploading related content so that it can be known by the public. The purpose of this study is to find out how the personal branding of beauty content creator Adhelia Fa on Instagram. This research approach is descriptive qualitative using qualitative content analysis methods and Hubert K. Rampersad's eleven criteria theory of personal branding. Data collection techniques were obtained from digital observation and attaching documentation in the form of screenshots of Adhelia Fa's Instagram content. The results showed that Adhelia Fa makes good use of Instagram to build her personal branding as a beauty content creator who is proud of her dark skin color and beautiful in her own way without following inappropriate beauty standards and her existence is recognized by the public audience of social media. Keywords: Beauty Content Creator, Content Analysis, Dark Skin, Instagram, Personal Branding